Historical and Political Allusions in the Drama “Hamletmachine” by Heiner Müller - Kolpakova, Svetlana Georgievna; Gataullina, Veronika Lubimovna; Smyslova, Ekaterina Vladimirovna (Journal of History Culture and Art Research, 2019)
In terms of postmodernism а classical plot becomes more active, mobile and begins to travel through the cultural discourses in different social and political channels, thereby indirectly achieving its full inner creative potential in the minds of "postmodern" readers. The paper focuses on Müller’s "Hamletmachine" which uses the Shakespearean plot. The authors of the article explore the new features introduced by the writer into the classic plot by placing it in postmodern principles (game, changes of meanings, rhizome, blissful ignorance of consumer society) which are woven together in a syncretic way. Müller masterfully uses these devices to transmit the political ideas and describe the history of communism and the historical events. The comparative method in combination with complex descriptive analysis of the text is chosen as the main methodology. The aim of the study is to find out what purposes and what political events Müller involves in the text of the drama.